2017
DOI: 10.1161/jaha.116.005149
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Migration in the Middle Cerebral Artery: Incidence, Imaging Signs, and Impact on Success of Endovascular Thrombectomy

Abstract: Background Thrombus migration ( TM ) in intracranial vessels during ischemic stroke has been reported in the form of case reports, but its incidence, impact on the technical success of subsequent endovascular thrombectomy and patients' outcome have never been studied systematically. Methods and Results Retrospective analysis was done of 409 patients with isolated middle cerebral artery occlusions treated with endovascular thrombectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 51 publications
0
45
2
Order By: Relevance
“…24 Conversely, the use of IVT before EVT may also pose a higher risk of emboli migrating to a previously uninvolved territory or thrombus migration to more distal arterial branches that cannot be reached with EVT, which is associated with a worse prognosis. 25 In our study, embolization to a new territory and thrombus migration were not documented. However, the postprocedural eTICI score of ≥2C was similar in both groups.…”
Section: Discussioncontrasting
confidence: 50%
“…24 Conversely, the use of IVT before EVT may also pose a higher risk of emboli migrating to a previously uninvolved territory or thrombus migration to more distal arterial branches that cannot be reached with EVT, which is associated with a worse prognosis. 25 In our study, embolization to a new territory and thrombus migration were not documented. However, the postprocedural eTICI score of ≥2C was similar in both groups.…”
Section: Discussioncontrasting
confidence: 50%
“…Our objective was to assess technical and safety aspects of EVT in patients with an M2 occlusion. 25 Second, ischemic stroke patients with a large-vessel occlusion who did not undergo EVT are not registered in the MR CLEAN Registry. Therefore, patients with distal M2 occlusions may have been excluded, which could have resulted in selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous clot migrations have also been observed in humans. 35 Using preinterventional computed tomographic angiography and MRA, Kaesmacher et al 35 showed that spontaneous clot migration occurs in 30% of patients who underwent endovascular thrombectomy, regardless of rt-PA administration. In our study, angiomaps of 3-D vascular networks were collected in real time (temporal resolution, 18 s) during stroke and reperfusion, which permitted the imaging of vascular network blood flow changes, thrombi formation, and bidirectional migration.…”
Section: Discussionmentioning
confidence: 99%